2020
DOI: 10.1126/sciadv.abc4254
|View full text |Cite
|
Sign up to set email alerts
|

A continuous pathway for fresh water along the East Greenland shelf

Abstract: Export from the Arctic and meltwater from the Greenland Ice Sheet together form a southward-flowing coastal current along the East Greenland shelf. This current transports enough fresh water to substantially alter the large-scale circulation of the North Atlantic, yet the coastal current’s origin and fate are poorly known due to our lack of knowledge concerning its north-south connectivity. Here, we demonstrate how the current negotiates the complex topography of Denmark Strait using in situ data and output fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
(59 reference statements)
1
34
0
Order By: Relevance
“…The EGCC (Bacon, 2002; Malmberg, 1967) is a fresh (practical salinity < 34), 20 km‐wide, surface‐intensified current, with a high‐velocity core (speeds > 1 m s −1 ) carrying arctic waters and Greenland runoff equatorward (Bacon et al., 2014; le Bras et al., 2018). Recent work (Foukal et al., 2020) showed that the EGCC extends along the whole east Greenland coast, while confirming that deep troughs south of Denmark strait divert part of the EGC into the coastal current (Sutherland & Cenedese, 2009; Sutherland & Pickart, 2008). Past Cape Farewell (CF), the EGC and EGCC were first thought to merge into the West Greenland Current (WGC; Bacon, 2002), but more recent studies argue that the EGCC keeps its identity as a coastal core to become the West Greenland Coastal Current (WGCC; Lin et al., 2018).…”
Section: Introductionmentioning
confidence: 85%
“…The EGCC (Bacon, 2002; Malmberg, 1967) is a fresh (practical salinity < 34), 20 km‐wide, surface‐intensified current, with a high‐velocity core (speeds > 1 m s −1 ) carrying arctic waters and Greenland runoff equatorward (Bacon et al., 2014; le Bras et al., 2018). Recent work (Foukal et al., 2020) showed that the EGCC extends along the whole east Greenland coast, while confirming that deep troughs south of Denmark strait divert part of the EGC into the coastal current (Sutherland & Cenedese, 2009; Sutherland & Pickart, 2008). Past Cape Farewell (CF), the EGC and EGCC were first thought to merge into the West Greenland Current (WGC; Bacon, 2002), but more recent studies argue that the EGCC keeps its identity as a coastal core to become the West Greenland Coastal Current (WGCC; Lin et al., 2018).…”
Section: Introductionmentioning
confidence: 85%
“…In the study of Foukal et al (2020) analyzing the East Greenland boundary current system, they defined the coastal current as the inner half of the shelf and fresher than 34 salinity. Based on Foukal et al (2020)'s definition, for all the sections indicated above except OSNAP East, we define the coastal current, and thus the transports, based on integrating the model velocity fields perpendicular to each section where the salinity is lower than 34.0 and bathymetry is shallower than 250 m (see Figure 3). As for OSNAP East, we use the position of the velocity minimum offshore of the EGCC, which we define as the 40 km mark, and also where the salinity is lower than 34.0, as the offshore edge of the coastal current.…”
Section: Transports Of the Coastal Current Systemmentioning
confidence: 99%
“…The edge of Greenland coastal current can be defined by isohaline only (34 salinity-e.g., Harden et al, 2014) or velocity only (e.g., Lin et al, 2018) or both (e.g., Sutherland et al, 2009). In the study of Foukal et al (2020) analyzing the East Greenland boundary current system, they defined the coastal current as the inner half of the shelf and fresher than 34 salinity. Based on Foukal et al (2020)'s definition, for all the sections indicated above except OSNAP East, we define the coastal current, and thus the transports, based on integrating the model velocity fields perpendicular to each section where the salinity is lower than 34.0 and bathymetry is shallower than 250 m (see Figure 3).…”
Section: Transports Of the Coastal Current Systemmentioning
confidence: 99%
“…Sea ice export through the Fram Strait plays a central role in the freshwater cycle connecting the Arctic and subarctic regions in the Northern Hemisphere 1 , 2 . Since the Arctic Ocean gathers 11% of the global river discharge into 3% area of the global ocean 3 , sea ice export, together with low salinity seawater carried by ocean currents, returns excess of the freshwater inputs toward lower latitudes 4 . The freshwater export mainly occurs in the Atlantic sector of the Arctic, thereby setting up surface stratification of the neighboring Nordic Seas and further downstream.…”
Section: Introductionmentioning
confidence: 99%